Rd Sharma Xi 2020 2021 _volume 1 Solutions for Class 12 Commerce Maths Chapter 21 Some Special Series are provided here with simple step-by-step explanations. These solutions for Some Special Series are extremely popular among Class 12 Commerce students for Maths Some Special Series Solutions come handy for quickly completing your homework and preparing for exams. All questions and answers from the Rd Sharma Xi 2020 2021 _volume 1 Book of Class 12 Commerce Maths Chapter 21 are provided here for you for free. You will also love the ad-free experience on Meritnation’s Rd Sharma Xi 2020 2021 _volume 1 Solutions. All Rd Sharma Xi 2020 2021 _volume 1 Solutions for class Class 12 Commerce Maths are prepared by experts and are 100% accurate.

#### Question 1:

13 + 33 + 53 + 73 + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}={\left(2n-1\right)}^{3}$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 2:

22 + 42 + 62 + 82 + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}={\left(2n\right)}^{2}$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 3:

1.2.5 + 2.3.6 + 3.4.7 + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 4:

1.2.4 + 2.3.7 +3.4.10 + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=n\left(n+1\right)\left(3n+1\right)=n\left(3{n}^{2}+4n+1\right)=\left(3{n}^{3}+4{n}^{2}+n\right)$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 5:

1 + (1 + 2) + (1 + 2 + 3) + (1 + 2 + 3 + 4) + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:
${T}_{n}=1+2+3+4+5+...+n=\frac{n\left(n+1\right)}{2}=\frac{{n}^{2}+n}{2}$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

$⇒{S}_{n}=\sum _{k=1}^{n}\left(\frac{{k}^{2}+k}{2}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{1}{2}\sum _{k=1}^{n}\left({k}^{2}+k\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{1}{2}\left[\frac{n\left(n+1\right)\left(2n+1\right)}{6}+\frac{n\left(n+1\right)}{2}\right]\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{4}\left(\frac{2n+1}{3}+1\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{4}\left(\frac{2n+4}{3}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)\left(2n+4\right)}{12}\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)\left(n+2\right)}{6}$

#### Question 6:

1 × 2 + 2 × 3 + 3 × 4 + 4 × 5 + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=n\left(n+1\right)={n}^{2}+n$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

$⇒{S}_{n}=\sum _{k=1}^{n}\left({k}^{2}+k\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\sum _{k=1}^{n}{k}^{2}+\sum _{k=1}^{n}k\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\left(\frac{n\left(n+1\right)\left(2n+1\right)}{6}+\frac{n\left(n+1\right)}{2}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{2}\left(\frac{2n+1}{3}+1\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{2}\left(\frac{2n+4}{3}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)\left(2n+4\right)}{6}\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)\left(n+2\right)}{3}$

#### Question 7:

3 × 12 + 5 ×22 + 7 × 32 + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=\left(2n+1\right){n}^{2}=2{n}^{3}+{n}^{2}$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

$⇒{S}_{n}=\sum _{k=1}^{n}\left(2{k}^{3}+{k}^{2}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\underset{k=1}{\overset{n}{2\sum }}{k}^{3}+\sum _{k=1}^{n}{k}^{2}\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\left[\frac{2{n}^{2}{\left(n+1\right)}^{2}}{4}+\frac{n\left(n+1\right)\left(2n+1\right)}{6}\right]\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\left[\frac{{n}^{2}{\left(n+1\right)}^{2}}{2}+\frac{n\left(n+1\right)\left(2n+1\right)}{6}\right]\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{2}\left[n\left(n+1\right)+\frac{2n+1}{3}\right]\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{2}\left(\frac{3{n}^{2}+3n+2n+1}{3}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{2}\left(\frac{3{n}^{2}+5n+1}{3}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{n\left(n+1\right)}{6}\left(3{n}^{2}+5n+1\right)$

#### Question 8:

Find the sum of the series whose nth term is:
(i) 2n2 − 3n + 5
(ii) 2n3 + 3n2 − 1
(iii) n3 − 3n
(iv) n (n + 1) (n + 4)
(v) (2n − 1)2

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

(i)
${T}_{n}=2{n}^{2}-3n+5$

Let ${S}_{n}$ be the sum of n terms of the given series.

Now,

(ii)
${T}_{n}=2{n}^{3}+3{n}^{2}-1$

Let ${S}_{n}$ be the sum of n terms of the given series.

Now,

(iii)
${T}_{n}={n}^{3}-{3}^{n}$

Let ${S}_{n}$ be the sum of n terms of the given series.

Now,

$⇒{S}_{n}=\sum _{k=1}^{n}\left({k}^{3}-{3}^{k}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\sum _{k=1}^{n}{k}^{3}-\sum _{k=1}^{n}{3}^{k}\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{{n}^{2}{\left(n+1\right)}^{2}}{4}-\left(3+{3}^{2}+{3}^{3}+{3}^{4}+...+{3}^{n}\right)\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{{n}^{2}{\left(n+1\right)}^{2}}{4}-\left[\frac{3\left({3}^{n}-1\right)}{3-1}\right]\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\frac{{n}^{2}{\left(n+1\right)}^{2}}{4}-\frac{3}{2}\left({3}^{n}-1\right)$

(iv)
${T}_{n}=n\left(n+1\right)\left(n+4\right)=\left({n}^{2}+n\right)\left(n+4\right)={n}^{3}+5{n}^{2}+4n$

Let ${S}_{n}$ be the sum of n terms of the given series.

Now,

(v)
${T}_{n}={\left(2n-1\right)}^{2}$

Let ${S}_{n}$ be the sum of n terms of the given series.

Now,

#### Question 9:

Find the 20th term and the sum of 20 terms of the series 2 × 4 + 4 × 6 + 6 × 8 + ...

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=2n\left(2n+2\right)=4{n}^{2}+4n$

For n = 20, we have:

Therefore, the 20th term of the given series is 1680.

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

$⇒{S}_{n}=\sum _{k=1}^{n}\left(4{k}^{2}+4k\right)\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}⇒{S}_{n}=\underset{k=1}{\overset{n}{4\sum }}{k}^{2}+4\sum _{k=1}^{n}k$

For n = 20, we have:

Hence, the sum of the first 20 terms of the series is 12320.

#### Question 1:

3 + 5 + 9 + 15 + 23 + ...

Let ${T}_{n}$ be the nth term and ${S}_{n}$ be the sum to n terms of the given series.

Thus, we have:

...(1)

Equation (1) can be rewritten as:

...(2)

On subtracting (2) from (1), we get:

The sequence of difference of successive terms is 2, 4, 6, 8,...
We observe that it is an AP with common difference 2 and first term 2.

Thus, we have:

$3+\left[\frac{\left(n-1\right)}{2}\left\{4+\left(n-2\right)2\right\}\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒3+\left[\frac{\left(n-1\right)}{2}\left(2n\right)\right]={T}_{n}\phantom{\rule{0ex}{0ex}}⇒3+n\left(n-1\right)={T}_{n}$

Now,

#### Question 2:

2 + 5 + 10 + 17 + 26 + ...

Let ${T}_{n}$ be the nth term and ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

...(1)

Equation (1) can be rewritten as:

...(2)

On subtracting (2) from (1), we get:

The sequence of difference of successive terms is 3, 5, 7, 9,...

We observe that it is an AP with common difference 2 and first term 3.

Thus, we have:

$2+\left[\frac{\left(n-1\right)}{2}\left\{6+\left(n-2\right)2\right\}\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒2+\left[{n}^{2}-1\right]={T}_{n}\phantom{\rule{0ex}{0ex}}⇒\left[{n}^{2}+1\right]={T}_{n}$

Now,

#### Question 3:

1 + 3 + 7 + 13 + 21 + ...

Let ${T}_{n}$ be the nth term and ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

...(1)

Equation (1) can be rewritten as:

...(2)

On subtracting (2) from (1), we get:

The sequence of difference of successive terms is 2, 4, 6, 8,...

We observe that it is an AP with common difference 2 and first term 2.

Thus, we have:

$1+\left[\frac{\left(n-1\right)}{2}\left\{4+\left(n-2\right)2\right\}\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒1+\left[{n}^{2}-n\right]={T}_{n}\phantom{\rule{0ex}{0ex}}⇒\left[{n}^{2}-n+1\right]={T}_{n}$

Now,

#### Question 4:

3 + 7 + 14 + 24 + 37 + ...

Let ${T}_{n}$ be the nth term and ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

...(1)

Equation (1) can be rewritten as:

...(2)

On subtracting (2) from (1), we get:

The sequence of difference of successive terms is 4, 7, 10, 13,...

We observe that it is an AP with common difference 3 and first term 4.

Thus, we have:

$3+\left[\frac{\left(n-1\right)}{2}\left\{8+\left(n-2\right)3\right\}\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒3+\left[\frac{\left(n-1\right)}{2}\left(3n+2\right)\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒\left[\frac{3{n}^{2}-n+4}{2}\right]={T}_{n}\phantom{\rule{0ex}{0ex}}⇒\left[\frac{3}{2}{n}^{2}-\frac{n}{2}+2\right]={T}_{n}$

Now,

#### Question 5:

1 + 3 + 6 + 10 + 15 + ...

Let ${T}_{n}$ be the nth term and ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

....(1)

Equation (1) can be rewritten as:

...(2)

On subtracting (2) from (1), we get:

The sequence of difference of successive terms is 2, 3, 4, 5,...

We observe that it is an AP with common difference 1 and first term 2.

Thus, we have:

$1+\left[\frac{\left(n-1\right)}{2}\left(4+\left(n-2\right)1\right)\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒1+\left[\frac{\left(n-1\right)}{2}\left(n+2\right)\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒\left[\frac{{n}^{2}+n}{2}\right]={T}_{n}$

Now,

#### Question 6:

1 + 4 + 13 + 40 + 121 + ...

Let ${T}_{n}$ be the nth term and ${S}_{n}$ be the sum to n terms of the given series.

Thus, we have:

${S}_{n}=1+4+13+40+121+...+{T}_{n-1}+{T}_{n}$       ...(1)

Equation (1) can be rewritten as:

...(2)

On subtracting (2) from (1), we get:

The sequence of difference between successive terms is 3, 9, 27, 81,...

We observe that it is a GP with common ratio 3 and first term 3.

Thus, we have:

$1+\left[\frac{3\left({3}^{n-1}-1\right)}{3-1}\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒1+\left[\frac{\left({3}^{n}-3\right)}{2}\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒\left(\frac{{3}^{n}}{2}-\frac{1}{2}\right)-{T}_{n}=0\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}⇒\left(\frac{{3}^{n}}{2}-\frac{1}{2}\right)={T}_{n}$

#### Question 7:

4 + 6 + 9 + 13 + 18 + ...

Let ${T}_{n}$ be the nth term and ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

${S}_{n}=4+6+9+13+18+...+{T}_{n-1}+{T}_{n}$       ...(1)

Equation (1) can be rewritten as:

...(2)

On subtracting (2) from (1), we get:

The sequence of difference between successive terms is 2, 3, 4, 5,...

We observe that it is an AP with common difference 1 and first term 2.

Now,

$4+\left[\frac{\left(n-1\right)}{2}\left\{4+\left(n-2\right)1\right\}\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒4+\left[\frac{\left(n-1\right)}{2}\left(n+2\right)\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒4+\left[\frac{{n}^{2}+n}{2}-1\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒\left[\frac{{n}^{2}}{2}+\frac{n}{2}+3\right]={T}_{n}$

#### Question 8:

2 + 4 + 7 + 11 + 16 + ...

Let ${S}_{n}$ be the sum of n terms and ${T}_{n}$ be the nth term of the given series.

Thus, we have:

...(1)

Equation (1) can be rewritten as:

${S}_{n}=2+4+7+11+16+...+{T}_{n-1}+{T}_{n}$            ...(2)

On subtracting (2) from (1), we get:

$⇒2+\left[\frac{\left(n-1\right)}{2}\left(4+\left(n-2\right)1\right)\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒2+\left[\frac{\left(n-1\right)}{2}\left(n+2\right)\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒2+\left[\frac{{n}^{2}+n}{2}-1\right]-{T}_{n}=0\phantom{\rule{0ex}{0ex}}⇒\left[\frac{{n}^{2}}{2}+\frac{n}{2}+1\right]={T}_{n}$

#### Question 9:

$\frac{1}{1.4}+\frac{1}{4.7}+\frac{1}{7.10}+...$

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 10:

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 1:

The sum to n terms of the series $\frac{1}{\sqrt{1}+\sqrt{3}}+\frac{1}{\sqrt{3}+\sqrt{5}}+\frac{1}{\sqrt{5}+\sqrt{7}}+....+....$ is
(a) $\sqrt{2n+1}$

(b) $\frac{1}{2}\sqrt{2n+1}$

(c) $\sqrt{2n+1}-1$

(d) $\frac{1}{2}\left|\sqrt{2n+1}-1\right|$

(d) $\frac{1}{2}\left\{\sqrt{2n+1}-1\right\}$

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:
${T}_{n}=\frac{1}{\sqrt{2n-1}+\sqrt{2n+1}}=\frac{\sqrt{2n+1}-\sqrt{2n-1}}{2}$

Now,

Let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 2:

The sum of the series is
(a)

(b)

(c)

(d) none of these

(c)

Let

#### Question 3:

The value of is equal to

(a)

(b)

(c)

(d) none of these

(b)

We have:

#### Question 4:

If ∑ n = 210, then ∑ n2 =
(a) 2870
(b) 2160
(c) 2970
(d) none of these

(a) 2870

Given:
n = 210

Now,

#### Question 5:

If Sn = , then Sn is equal to
(a) 2nn − 1

(b) $1-\frac{1}{{2}^{n}}$

(c) $n-1+\frac{1}{{2}^{n}}$

(d) 2n − 1

(c) $n-1+\frac{1}{{2}^{n}}$

We have:
Sn =

#### Question 6:

If $1+\frac{1+2}{2}+\frac{1+2+3}{3}+....$ to n terms is S, then S is equal to

(a)

(b)

(c)

(d) n2

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=\frac{1+2+3+4+5+...+n}{n}=\frac{n\left(n+1\right)}{2n}=\frac{n}{2}+\frac{1}{2}$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 7:

Sum of n terms of the series $\sqrt{2}+\sqrt{8}+\sqrt{18}+\sqrt{32}+$ .... is
(a)

(b) 2n (n + 1)

(c)

(d) 1

(c)

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=\sqrt{2×{n}^{2}}=n\sqrt{2}$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 8:

The sum of 10 terms of the series $\sqrt{2}+\sqrt{6}+\sqrt{18}+$.... is
(a)

(b)

(c) $\frac{121}{\sqrt{3}-1}$

(d)

(a)

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=\sqrt{2×{3}^{n-1}}=\sqrt{2}\left(\sqrt{{3}^{n-1}}\right)$

Now, let ${S}_{10}$ be the sum of 10 terms of the given series.

Thus, we have:

#### Question 9:

The sum of the series 12 + 32 + 52 + ... to n terms is
(a)

(b)

(c)

(d) $\frac{\left(2n+1{\right)}^{3}}{3}$

(b)

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}={\left(2n-1\right)}^{2}=4{n}^{2}+1-4n$

Now, let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 10:

The sum of the series $\frac{2}{3}+\frac{8}{9}+\frac{26}{27}+\frac{80}{81}+$..... to n terms is
(a) $n-\frac{1}{2}\left({3}^{-n}-1\right)$

(b)$n-\frac{1}{2}\left(1-{3}^{-n}\right)$

(c) $n+\frac{1}{2}\left({3}^{n}-1\right)$

(d) $n-\frac{1}{2}\left({3}^{n}-1\right)$

(b) $n-\frac{1}{2}\left(1-{3}^{-n}\right)$

Let ${T}_{n}$ be the nth term of the given series.

Thus, we have:

${T}_{n}=\frac{{3}^{n}-1}{{3}^{n}}=1-\frac{1}{{3}^{n}}$

Now,

Let ${S}_{n}$ be the sum of n terms of the given series.

Thus, we have:

#### Question 11:

Let Sn denote the sum of the cubes of the first n natural numbers and Sn denote the sum of the first natural numbers. Then equals
(a) $\frac{n\left(n+1\right)\left(n+2\right)}{6}$

(b) $\frac{n\left(n+1\right)}{2}$

(c) $\frac{{n}^{2}+3n+2}{2}$

(d) None of these

Let Sn denote the sum of the cubes of the first n natural numbers and Sn denotes the sum of the first n natural number 1.
Then
; formula for sum of cubes.

${S}_{n}=\frac{n\left(n+1\right)}{2}$        ; formula form sum of first n natural numbers.

Hence, the correct answer is option A.

#### Question 1:

If S1 and S2 denote respectively the sum of first 100 natural numbers and the sum of their cubes, then the relation between S1 and S2 is __________.

Let
S1 : the sum of first 100 natural numbers
S2 : the sum of their cubes.

#### Question 2:

Let Sn and S'4 denote respectively the sum and the sum of the squares of first n natural numbers. If Then a1, a2, a3,_____, an, _____ forms an ______ with ______ .

Sn : The sum of first n natural numbers .
Sn : Sum of squares of first n natural numbers.
If an$\frac{{S}_{n}\text{'}}{{S}_{n}}$ ; nN.

Hence, common difference is
a2 − a1$\frac{5}{3}-1=\frac{2}{3}$
aa$\frac{7}{3}-\frac{5}{3}=\frac{2}{3}$
Hence, common difference of  A.? is $\frac{2}{3}$.

#### Question 3:

The sum of first 25 odd natural numbers is _________.

Sum of for 25 odd numbers :-
Let S denote the sum of  first 25 odd numbers
Here number are 1, 3, 5, 7, 9 --------- 49.
Here  first term is 1

last term is 49
Common difference d is 2
n = 25

i.e sum of first 25 odd numbers = 625.

#### Question 4:

The value of $\sum _{r=1}^{n}\left\{\left(2r-1\right)+\frac{1}{{2}^{r}}\right\}$ is _______________.

Here  first term is 1

last term is 2n − 1
i.e sum is $\frac{n}{2}$ (first term + last term)

#### Question 5:

The sum of n terms of the series 22 + 42 + 62 +......, is _______________.

Sum of n terms of series  22 + 42 + 62 + .........
Let nth term of series be denoted byn
i.e n = (2n)2

i.e sum of n terms of 22 + 42 + 62 =

#### Question 6:

14 + 24 + 34 +______+ n4 = _______________.

Ans

#### Question 7:

If S2 and S4 denote respectively the sum of the squares and the sum of the fourth powers of first n natural numbers, then $\frac{{S}_{4}}{{S}_{2}}=$_______________.

S2 : Sum of the squares of first n natural numbers.
S: Sum of the fourth powers of first n natural numbers.
To find :- $\frac{{S}_{4}}{{S}_{2}}$

#### Question 8:

The value of $\frac{{1}^{3}+{2}^{3}+{3}^{3}+______+{10}^{3}}{1+2+3+______+10}$ ______________.

#### Question 9:

If the sum of the squares of first n natural numbers exceeds their sum by 330, then n = _______________.

Sum of squares of first n natural numbers is
Sum of first n natural number is
According to given condition,

i.e n3 − 10n2 + 10n2 − n − 990 = 0 − 99n + 99n
i.e n(n − 10) + 10n2 − 100n − 990 + 99n = 0
i.e n(n − 10) + 10n (n − 10) + 99(n−10) = 0
i.e (n − 10) (n2 + 10+ 99) = 0
n = 10

#### Question 10:

The sum of n terms of the series $\frac{3}{{1}^{2}}+\frac{5}{{1}^{2}+{2}^{2}}+\frac{7}{{1}^{2}+{2}^{2}+{3}^{2}}+$_________ is _______________.

Sum of n term of
here nth term tn for above series is

#### Question 1:

Write the sum of the series 2 + 4 + 6 + 8 + ... + 2n.

${S}_{n}=2+4+6+8+...+2n$

#### Question 2:

Write the sum of the series 12 − 22 + 32 − 42 + 52 − 62 + ... + (2n − 1)2 − (2n)2.

The given series can be rewritten as:

$=-\left[3+7+11+...+\left(4n-1\right)\right]\phantom{\rule{0ex}{0ex}}=-\left[\frac{n}{2}\left\{3×2+\left(n-1\right)4\right\}\right]\phantom{\rule{0ex}{0ex}}=-\left[\frac{n}{2}\left(4n+2\right)\right]\phantom{\rule{0ex}{0ex}}=-n\left(2n+1\right)$

#### Question 3:

Write the sum to n terms of a series whose rth term is r + 2r.

Series whose rth term is r + 2r:

$\left(1+{2}^{1}\right)+\left(2+{2}^{2}\right)+\left(3+{2}^{3}\right)+\left(4+{2}^{4}\right)+...+\left(n+{2}^{n}\right)$

Thus, we have:

If .

#### Question 5:

If the sum of first n even natural numbers is equal to k times the sum of first n odd natural numbers, then write the value of k.

According to the question,

#### Question 6:

Write the sum of 20 terms of the series $1+\frac{1}{2}\left(1+2\right)+\frac{1}{3}\left(1+2+3\right)+....$

Let the nth term be ${a}_{n}$.
Here,
${a}_{n}=\frac{1}{n}\left(1+2+3+...+n\right)=\left(\frac{n+1}{2}\right)$
We know:
${S}_{n}=\sum _{k=1}^{n}{a}_{k}$
Thus, we have:
${S}_{20}=\sum _{k=1}^{20}{a}_{k}$

#### Question 7:

Write the 50th term of the series 2 + 3 + 6 + 11 + 18 + ...

So, the 50th term of the given series is 2403.

#### Question 8:

Let Sn denote the sum of the cubes of first n natural numbers and sn denote the sum of first n natural numbers. Then, write the value of
$\sum _{r=1}^{n}\frac{{S}_{r}}{{s}_{r}}$.